Human resource management from Islamic perspective: experiences of GLCs / Idris Osman, Mohd Halim Mahphoth and Maryam Jameelah Mohd Hashim - Osman, Idris; Mahphoth, Mohd Halim; Mohd Hashim, Maryam Jameelah (2012)
Muslims in developing nations faced the greatest challenge where globalization becomes a threat that must be executed with development (Dr. Mahathir, 2000). Globalization has influenced local employees to adapt Western management (Branine, 2011) and this issue increasingly resulted inconsistency of aspects, religion and business practices. Khan et al (2010), Metcalfe (2007), Maznil (1997), Tayeb (1997) and Abuznaid (2006) believe religion plays important and significant roles for organizations to gain competitiveness. In Muslims countries, Islamic principles affect human behaviors. It must be maintained by the Quran and Sunnah to treat employees fairly and justly. Human resource recognised as a source of competitive advantage in organizations (Khan et al, 2010; Haslinda, 2009; Junaidah, 2010; Hamid & Zhan, 2008). Khalid et al (2008) agreed to manage human resource in global competitiveness must be considered the cultural awareness, especially in religion. Thus, interference of religion into human resource management (HRM) proves to maintain competitive advantage and promoting a good relationship between employer and employee in organizations. Nik Mutasim (2009) and Khan (2010) found the positive relationship between Islamic principles and human resource management. Junaidah (2010) added is an obligation for organizations to practice Islamic principles to manage human resource. Islamic HRM have concerned the justice and fairness (Abulhassan, 2006). According Junaidah (2008), managing human resource in Islamic approaches does influence organizational justices. Islam a complete religion of life and objectively create the universe to uphold justice and truth (Mahathir, 2000).